Calcined polycyclotriphosphazene@NiAl-LDH@RhxNi1-x: A novel hierarchically oriented composition tunable catalyst for green and sustainable hydrogen generation. Issue 3 (June 2022) - Abbas, Yasir; Zuhra, Zareen; Majeed, Sahresh; Khan, Muhammad Shuaib; Basharat, Majid; Tyagi, Deependra; Ali, Shafqat; Wu, Zhanpeng; Liu, Zhaojun
Abstract: The ever decreasing amount of fossil fuels and increasing environmental pollution are alarming threats for green and sustainable future. Designing a new catalyst is, therefore, of paramount significance in the quest to discover sustainable, robust, and environmentally benign materials for clean and sustainable energy generation. Herein, we developed a hierarchically oriented catalyst of calcined poly(ferrocenedimethano)-cyclotriphosphazene-microspheres (CPFC-MS) supported with nickel-aluminum layered double hydroxide and decorated with nanoparticles (NPs) of rhodium-nickel, NiAl-LDH@Rh x Ni1 - x ( x = 2.06–6.75), for H2 generation from ammonia borane (AB) hydrolysis. The highly active catalyst was characterized by scanning electron microscopy (SEM), Raman spectroscopy, high-resolution transmission electron microscopy (HRTEM) and TEM, energy dispersive X-ray spectroscopy (EDX), fourier transform infrared (FTIR), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS). The as-fabricated CPFC-MS@NiAl-LDH@Rh x Ni1- x ( x = 2.06–6.75) catalysts were tested for AB hydrolysis and the results showed remarkable performance and higher stability for H2 generation. The CPFC-MS@NiAl-LDH@Rh2.06 Ni7.32 catalyst, having the lowest Rh-contents, exhibited maximum H2 generation with a turn over frequency (TOF) of 780 mol H2 hr −1 mol Rh −1 and an activation energy (Ea ) of 40.3 kJ/mol with excellent sustainability. The superior activity is ascribed to the synergetic effect between RhNi NPs and their well-dispersion over hierarchically oriented CPFC-MS@NiAl-LDH support, while higher stability due to LDH-AlNi/RhNi attractions. This work will provide new opportunities for polyphosphazenes and LDH derived hierarchically oriented sustainable catalysts for green energy production for sustainable future. Graphical Abstract: ga1